KEBERLAKUAN YURIDIS PERATURAN DESA DALAM PERSPEKTIF ASAS FORMAL KELEMBAGAAN PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Muhammad Syirazi Neyasyah (University Of Bengkulu Law Journal, 2019)
ABSTRACTThis paper raises the legal issue regarding the juridical enactment of Village Regulations seen from the perspective of the formal principle of the institution of the formation of legislation in accordance with the principles of the formation of legislation stipulated in Law Number 12 of 2011 concerning the Establishment of Legislation. Identification of the problem under study is how does the juridical enactment of Village Regulations be seen from the perspective of the formal principle of the formation of legislation? Can the Village Consultative Body as a village head partner in forming Village Regulations be qualified as an institution for establishing village legislation? This research is normative legal research, using a statute approach, utilizing primary, secondary and tertiary legal materials. Analysis of legal material is carried out using qualitative analysis, with deductive reasoning. The results showed that the juridical enactment of Village Regulations was viewed from the perspective of the formal institutional principle of formation, because the Village Consultative Body could not qualify as a Village Representative Body, whereas according to the formal principle of establishing good village regulations, Village Regulations were made by the Village Representative Body together with the head village. The village does not have a Village Representative Body, but a Village Consultative Body. Therefore the Village Regulations established by the Village Consultative Body together with the village head did not fulfill the principle of juridical enforceability, which emphasized that the legislation must be formed by the appropriate forming institution, in this case, the Village Representative Body together with the village head. Keywords: enforceability, juridical, formal principles, institutions, village regulations.ABSTRAKTulisan ini mengangkat isu hukum mengenai keberlakuan yuridis Peraturan Desa dilihat dari perspektif asas formal kelembagaan pembentukan peraturan perundang-undangan sesuai dengan asas pembentukan peraturan perundang-undangan yang diatur dalam Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan. Identifikasi masalah yang diteliti yaitu bagaimanakah keberlakuan yuridis  Peraturan Desa dilihat dari perspektif asas formal kelembagaan pembentukan  peraturan perundang-undangan? Apakah Badan Permusyawaratan Desa sebagai mitra kepala desa dalam membentuk Peraturan Desa dapat dikualifikasikan sebagai kelembagaan pembentukan peraturan perundang-undangan di desa? Penelitian ini merupakan penelitian hukum normatif, dengan menggunakan pendekatan peraturan perundang-undangan (statute approach), memanfaatkan bahan hukum primer, sekunder dan bahan hukum tersier. Analisis bahan hukum dilakukan dengan menggunakan analisis kualitatif, dengan penalaran deduktif. Hasil penelitian menunjukkan bahwa keberlakuan yuridis Peraturan Desa Peraturan Desa dilihat dari perspektif asas formal kelembagaan pembentukannya, karena Badan Permusyawaratan Desa tidak dapat dikualifikasikan sebagai Badan Perwakilan Desa, padahal menurut asas formal pembentukan peraturan desa yang baik, Peraturan Desa dibuat oleh Badan Perwakilan Desa  bersama dengan kepala desa. Desa tidak memiliki Badan Perwakilan Desa, melainkan Badan Permusyawaratan Desa. Oleh karena itu Peraturan Desa yang dibentuk Badan Permusyawaratan Desa  bersama kepala desa tidak memenuhi asas keberlakuan yuridis, yang menekankan bahwa Peraturan perundang-undangan harus dibentuk oleh kelembagaan pembentuk yang tepat, dalam hal ini Badan Perwakilan Desa  bersama dengan kepala desa. Kata Kunci: keberlakuan, yuridis,  asas formal, kelembagaan, peraturan desa.